2004
DOI: 10.1108/09513570410545803
|View full text |Cite
|
Sign up to set email alerts
|

God's fund managers

Abstract: While the literature contains a number of studies of ethical investment funds, relatively little is known about church investment processes and practices despite the significant role they have played in the development of the sector. This paper attempts to address this lacuna by studying the ethical investment programmes of two UK churches: the Methodist Church and the Church of England. The paper initially explores the relationship between the Judaeo-Christian church and the development of the ethical investm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 39 publications
1
15
0
1
Order By: Relevance
“…The social context perspective is increasingly being confronted by most notably studies in Christian communities that they found accounting can be part of the sacred sphere of life and be considered as an essential part in the management process to ensure the accountability in religious organization (Irvine, 2005;Irvine, 2011;Lightbody, 2000;Jacobs, 2004;Kreander, 2004;Quattrone, 2015;Funnel, 2015).…”
Section: Theological Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…The social context perspective is increasingly being confronted by most notably studies in Christian communities that they found accounting can be part of the sacred sphere of life and be considered as an essential part in the management process to ensure the accountability in religious organization (Irvine, 2005;Irvine, 2011;Lightbody, 2000;Jacobs, 2004;Kreander, 2004;Quattrone, 2015;Funnel, 2015).…”
Section: Theological Perspectivementioning
confidence: 99%
“…This paper asserts that Christ the transformer of culture typology is relevant to be adopted in ECCT Kota Baru Church since the vision of this church is to answer the needs of the society through its five services, called "PancaTugas", which comprises of Koinonia, Merturia, Diakonia, Liturgia and Oikonomia (ECCT Kota Baru Kupang, 2016). This is based on principle theological values of creationism, witness, agapism, engagement and stewardship (Kreander, 2004). Transforming Christian values should be embedded in the church budget and program executions (Parker, 2001;Parker, 2002;Benu, 2017;Tumiwa et.al., 2015).…”
Section: Niebuhr Theory and Its Application On Accountingmentioning
confidence: 99%
See 2 more Smart Citations
“…The Church of England (CofE) has a considerably longer history than megachurches and, hence, has attracted a number of research investigations, but as with megachurches, the research has a marginal relevance to the church's use of the web or social media. For example, earlier studies have explored the Church's accounting systems (Laughlin, 1988), investment practices (Kreander, McPhail, & Molyneaux, 2004) and women's contribution and experiences (Levitt, 2003;Sani & Reicher, 2000). Adopting a more explicitly marketing and communications perspective, Muskett…”
Section: Previous Research On Churchesmentioning
confidence: 99%